Light to moderate amount of lifetime alcohol consumption and risk of cancer in Japan. Issue 5 (9th December 2019) - Zaitsu, Masayoshi; Takeuchi, Takumi; Kobayashi, Yasuki; Kawachi, Ichiro
Abstract : Background: Even light to moderate alcohol consumption has been shown to increase cancer incidence. However, this association has not been well characterized in Japan. Methods: Based on a nationwide, hospital‐based data set (2005‐2016), a multicenter case‐control study was conducted (63, 232 cancer cases and 63, 232 controls matched for sex, age, admission date, and admitting hospital). The total amount of lifetime alcohol consumption (drink‐years) was recalled for each patient by multiplication of the daily amount of standardized alcohol use (drinks per day) and the duration of drinking (years). Odds ratios (ORs) were estimated for overall and specific cancer sites via conditional logistic regression with restricted cubic splines, with adjustments made for smoking, occupational class, and comorbidities. Lifetime abstainers served as the reference group. Results: Spline curves showed a dose‐response association with overall cancer risk: the minimum risk was at 0 drink‐years, and the OR at 10 drink‐years was 1.05 (95% confidence interval [CI], 1.04‐1.06). In comparison with lifetime abstainers, the OR for >0 to 20 drink‐years was 1.06 (95% CI, 1.01‐1.11). Those who drank 2 drinks or fewer per day had elevated odds for overall cancer risk across all duration‐of‐drinking categories. The same patterns were observed at light to moderate levels of drinking for most gastrointestinal/aerodigestive cancers as well as breast and prostate cancers. Analyses stratified by sex, different drinking/smoking behaviors, and occupational class mostly showed the same patterns for overall cancer incidence associated with light to moderate levels of drinking. Conclusions: In Japan, even light to moderate alcohol consumption appears to be associated with elevated cancer risks. Abstract : Light to moderate levels of lifetime drinking may increase the overall cancer risk with a dose‐response association, and the overall cancer risk appears to be lowest with zero alcohol consumption in Japan. The elevated overall cancer risk appears to be explained by alcohol‐related cancer risk across common sites, including the colorectum, stomach, breast, prostate, and esophagus.